An empirical investigation of Bangladesh’s inflation dynamics: evaluating persistence and identifying structural breaks - Mujtaba Rafid Rafa; Syed Abul Basher (Humanities & Social Sciences Communications)
Abstract We quantify two hypotheses: the “Friedman-Ball Hypothesis” and the “Cukierman-Meltzer Hypothesis,” in the context of Bangladesh. The first posits that an increase in inflation leads to greater inflation uncertainty, while the second asserts that inflation uncertainty causes an increase in inflation. Using monthly inflation data from June 1997 to July 2021, we find evidence supporting both hypotheses. Our analysis of inflation persistence and structural breaks reveals that inflation in Bangladesh exhibits high persistence throughout the entire sample period, but there is a decrease in persistence in two of the sub-samples after the breaks in March 2007 and April 2012. Moreover, Bangladesh’s inflation persistence is comparable to, and at times even lower than, that of its South and Southeast Asian neighboring countries. As policy implications of our findings, we emphasize the need for a more nuanced approach to monetary policy, including proactive interest rate management, implementation of a Medium-Term Fiscal Framework, and the development of a flexible monetary policy strategy tailored to Bangladesh’s unique economic circumstances.